The absolutely true diary of a part-time Indian - Alexie, Sherman 1966-; Forney, Ellen (New York Little, Brown, 2007)
Budding cartoonist Junior leaves his troubled school on the Spokane Indian Reservation to attend an all-white farm town school where the only other Indian is the school mascot
13
Keywords: Spokane Indians -- Juvenile fiction; Diaries -- Fiction; Indian reservations -- Fiction; Indians of North America -- Washington (State) -- Fiction; Race relations -- Fiction; Spokane Indians -- Fiction